The domestication of the subjectivity in the convent. Barroque nuns without a seal: From Monza to Mexico or from Gertrude to Sor Juana (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article studies the topic of the literary presentation of femininesubjectivity, both from the so-called ‘outside’ to the ‘inside’of the text and from the ‘inside’ to the ‘outside’. The former perspective is studied here in the literary creation of the character of the Monza nun, by Manzoni, who based his story on the proceedings of a real trial of a nun. The latter perspective is analyzed in the discursive creation that Sor Juana makes of herself. The analysis aims to trace the taming process that molded those subjectivities in the convent, a place where the desires and/or thethoughts of those women was subdued to the rules of a rationalized economy, whose norms where regulated and controlled by men.
Keywords: feminine subjectivity; Juana Inés de la Cruz; Manzoni; historiographic metafiction